How do we solve `2x+3b+56=29`  ?

1 Answer | Add Yours

lemjay's profile pic

lemjay | High School Teacher | (Level 3) Senior Educator

Posted on

`2x+3b+56=29`

(a) If we are going to solve for x, the steps are:

> Isolate the term 2x. So move 3b and 26 to the right side of the equation.

   `2x + 3b + 56 = 29`

        `- 3b``- 56`  `-56``- 3b`

  `--------------`

      `2x + 0 + 0 = -27-3b`

                `2x= -27-3b`

> Then, isolate x. So move 2 to the right side.

                `(2x)/2 = (-27-3b)/2`

                 `x = -(3b+27)/2`

Hence, `x= -(3b+27)/2` .

(b) If we are going to solve for b, same steps above. But here, it is the variable b that we need to have at the left side of the equation.

> Isolate 3b. 

    `2x + 3b + 56 `  `=`   `29`

  `-2x`       `-56`       `-56`  `- 2x`

 `------------------`

          `0 +3b + 0 = -27-2x`

                    `3b = -27-2x`

> Then, isolate b.

                    `(3b)/3 = (-27-2x)/3`

                      `b = (-27-2x)/3`

                     ` b=-(2x+27)/3`

Hence, `b=-(2x+27)/3`  .           

We’ve answered 318,928 questions. We can answer yours, too.

Ask a question